2018
DOI: 10.1007/s00221-018-5309-0
|View full text |Cite
|
Sign up to set email alerts
|

Timing of grip and goal activation during action perception: a priming study

Abstract: Several models of action recognition acknowledge the involvement of distinct grip and goal representations in the processing of others' actions. Yet, their functional role and temporal organization are still debated. The present priming study aimed at evaluating the relative timing of grip and goal activation during the processing of photographs of object-directed actions. Action could be correct or incorrect owing to grip and/or goal violations. Twenty-eight (Experiment 1) and 25 (Experiment 2) healthy adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 57 publications
4
24
0
Order By: Relevance
“…Therefore, both motor acts and action goal dimensions may independently contribute to modulations of the N400 component. This further suggests that the two dimensions can be dissociated and reflected in the components of visual ERPs, hence complementing previous behavioural results 18,32 . Focusing on the recognition of hand-object actions (i.e., does the action picture display a typical use of the object), Chang et al 33 reported modulations of the N300 component by the processing of action violations (e.g., using a precision grip on an upright pencil versus using a power grasp on an upside-down pencil).…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Therefore, both motor acts and action goal dimensions may independently contribute to modulations of the N400 component. This further suggests that the two dimensions can be dissociated and reflected in the components of visual ERPs, hence complementing previous behavioural results 18,32 . Focusing on the recognition of hand-object actions (i.e., does the action picture display a typical use of the object), Chang et al 33 reported modulations of the N300 component by the processing of action violations (e.g., using a precision grip on an upright pencil versus using a power grasp on an upside-down pencil).…”
supporting
confidence: 86%
“…The rather low performances in the task most likely reflect the important working memory load induced by the response procedure. Indeed, our previous experiments with similar tasks and design revealed high-level of accuracy in performing perceptual judgements 18,41 . Similarly, perceptual judgements were rather high (90%) in the pre-test (cf.…”
Section: Resultsmentioning
confidence: 77%
“…In a recent behavioral study, we reported more direct evidence in favor of the goal-first hypothesis. The recognition of visual actions was facilitated after being briefly primed (66 ms) by actions showing the same action goal, but not the same action grip (Decroix & Kalénine, 2018). This result demonstrated that goal-related information is used earlier that information about visual kinematics when the task puts minimal requirement on the visuo-attentional system (i.e., central presentation of one action picture at a time).…”
Section: Discussionmentioning
confidence: 81%
“…Prior work has shown that people integrate object and action kinematic information to derive the likely goal of observed actions, even while the action is still ongoing ( Ambrosini et al, 2011 ; Bach et al, 2011 ; Decroix & Kalénine, 2018 ; Eshuis, Coventry, & Vulchanova, 2009 ; for a review, see Bach et al, 2014 ). Here, we tested the hypothesis of predictive processing models ( Bach & Schenke, 2017 ; Hudson, Nicholson, Ellis et al, 2016 ; Hudson, Nicholson, Simpson et al, 2016 ) that such goal inferences are immediately translated into perceptual predictions about the actions future path toward the inferred goal, and bias perceptual judgments toward these expected trajectories.…”
Section: Discussionmentioning
confidence: 99%